Preparation of Symmetric and Nonsymmetric Imines from Primary Benzyl Amines by Means of an Oxidative Functionalization Reaction Using an Oxoammonium Salt Bearing the Nitrate Anion - Sharma, Manisha; Leadbeater, Nicholas E. (Synlett, 2025)
A methodology for the preparation of symmetric and nonsymmetric imines from primary benzyl amines is reported. The approach employs 4-acetamido-2,2,6,6-tetramethylpiperidin-1-oxoammonium nitrate (4-acetamido TEMPO), a recyclable oxoammonium salt bearing the nitrate anion, as the primary oxidant. It proves effective for a range of amine substrates bearing electron-withdrawing and -donating groups at ortho, meta, or para positions, along with disubstituted amines with the desired products being formed in good to excellent yield (75–97%). Nonsymmetric imine formation is achieved using aniline as a coupling partner with benzyl amines.
Keywords: oxidation; oxoammonium salt; amines; imines; water; recyclable